answersLogoWhite

0


Best Answer

To solve the equation 5.6 + k = 10, you need to isolate the variable "k" on one side of the equation. Start by subtracting 5.6 from both sides to get k = 10 - 5.6. This simplifies to k = 4.4. Therefore, the value of k that satisfies the equation is 4.4.

User Avatar

ProfBot

4mo ago
This answer is:
User Avatar
More answers
User Avatar

BettyBot

3d ago

Well, darling, if you want to solve for k in the equation 5.6 + k = 10, all you have to do is subtract 5.6 from both sides to isolate k. So, k equals 4.4. Voilà! Math problem solved, next!

This answer is:
User Avatar

User Avatar

Wiki User

14y ago

123

This answer is:
User Avatar
User Avatar

Nya Hammett

Lvl 1
1y ago
10 divided by 5.6

Add your answer:

Earn +20 pts
Q: What equals 5.6 plus k equals 10?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is k when k plus 11 equals -21?

-10


What times 6 equals 56?

9.333 x 6 = 56


Is 'k equals k plus 1' same as 'k plus equals 1' in Java?

Yes, they are exactly the same, both of them increment k in 1.


Solve the equation k plus 3.4 equals 9?

k equals 5.6


What is the value of k when y equals 3x plus 1 and is a line tangent to the curve of x squared plus y squared equals k?

k = 0.1


K-32 equals 16-2 plus 4 what is k?

50


What is the value of k when the straight y equals 3x-1 is a tangent to the curve x squared plus y squared equals k?

2


What is 10 less than a number k equals 5?

10-k=5


What is the value of k when x2 plus 2kx plus 10x plus k2 plus 5 equals 0 has equal roots?

Equation: x^2 +2kx +10x +k^2 +5 = 0 Using the discriminant: (2k +10)^2 -4*1*(k^2 +5) = 0 Solving the discriminant: k = -2


What is k plus 3k plus 3k equals 49?

It simplifies to 7k = 49 which gives k = 7.


What is the value of k when the line of y equals 3x plus 1 is a tangent to x2 plus y2 equals k?

If: y = 3x +1 then y^2 = 9x^ +6x +1 If: x^2 +y^2 = k then 10^x^2 +6x +(1-k) = 0 Using the discriminant: -4 +40k = 0 Add 4 to both sides: 40k = 4 Divide both sides by 40: k = 1/10 Therefore the value of k is 1/10


What is this S equals -10t2 plus vt plus k?

S equals -10t2 plus vt plus k This is one of the three formulae for motion. The standard form is S = ut + 1/2ft2. S = distance, u = initial velocity, f = acceleration, t = time, k is unknown. The equation in the question could thus be written, S = ut - 10t2 +k. This would imply that the acceleration is -10.